Comparison of Supraclavicular Oblique Incision With Traditional Low Collar Incision Approach for Thyroidectomy in Differentiated Thyroid Cancer - Jiang, Bo; Qu, Cheng; Jiang, Chaoyu; Zhang, Chen; Shen, Song; Luo, Yuqian; Su, Lei (Frontiers in Oncology, 2022)
Background: Various incisions and approaches have been developed for thyroidectomy in differentiated thyroid cancer (DTC). Supraclavicular oblique incision thyroidectomy (SOIT) has been applied in DTC patients over the past ten years. However, whether the approach is safe and effective for thyroidectomy is still not confirmed since the small number of studies. Aim: This study aimed to compare the surgical and patient-related outcomes between SOIT and traditional low collar incision thyroidectomy (TLCIT) in DTC. Methods: We retrospectively screened all DTC patients receiving thyroid lobectomy from October 2020 to October 2021. The surgical results and patient-related outcomes assessed at 1 and 6 months after surgery by questionnaire between SOIT group and TLCIT group were compared. Results: We finally included 128 patients in this study, of whom 38 patients (30.5%) were operated with SOIT, and 89 patients (69.5%) with TLCIT. There were no significant differences in demographic characteristics and thyroid features. SOIT group were operated with a shorter neck incision (4.4±0.7 vs. 5.0±1.0 cm, p=0.002) with a similar operative time (61.9±12.1 vs. 59.9±15.0 min, p=0.425). SOIT group were found with a shorter duration of postoperative drainage (2.4±0.5 vs. 2.7±0.9 days, p=0.019), shorter postoperative hospitalization (3.2±0.5 vs. 3.6±0.9 days p=0.006) and less volume of postoperative drainage (48.4±24.6 vs. 60.3±22.8 ml, p=0.040). Regarding 1month follow-up outcomes following surgery, SOIT shows better performance in preventing hypoparathyroidism (p=0.026), abnormal neck sensation (p=0.010) and improving cosmetic satisfaction (p=0.036) than TLCIT. For six months follow-up, SOIT group were feedback with the better cosmetic satisfaction (p<0.001) and lower percent of abnormal neck sensation (p=0.031) and movement (p=0.005). Conclusion: Our study suggests that minimally invasive surgery through the supraclavicular oblique incision provides superior surgical and patient-related outcomes compared to those in a Traditional low collar incision in DTC.